THE FACE AND CONTENT VALIDITY OF AN INSTRUMENT FOR MEASURING FINANCIAL RISK TOLERANCE (Journal of Computational Innovation and Analytics (JCIA), 2023)
Accurate evaluation of investment risk tolerance is critical in an investment decision-making process because a mismatch between the risk an investor could tolerate and the risk-return expectations could lead to frustration towards the actual financial gains or financial losses. This study aims to develop a valid instrument (or scale) for self-directed Malaysian investors to measure financial risk tolerance based on four main constructs, i.e., risk attitude, risk propensity, risk capacity, and financial literacy. An initial 36-item instrument was developed based on the assessment framework from Cordell (2001), which subsequently was examined by four lay experts for face validity. Consequently, according to Andrian et al. (2018), seven professional experts, comprising theoretical, industry practitioner, and psychometric experts, were involved in reviewing the relevancy of the content of each item towards measuring financial or investment risk tolerance level. As a result, the instrument is deemed to have a good face value, with 94.4% of the items rated highly at 4 or 3 (out of the maximum rating of 4) by lay experts. Out of the 36 items, only 5.56% are rated 1 or 2, and 16.7% of the items require revision in terms of their face value and clarity. The content validity exercise resulted in high scores of more than 0.83 cut scores based on Lynn (1986) for the scale content validity index (S-CVI), with nine items recorded as item content validity index (I-CVI) below 0.83. The S-CVI improved further to 0.90 after the removal of items with low I-CVI. The findings have also successfully produced a valid instrument that can measure the financial risk tolerance level of investors in Malaysia.